THE ROLE OF KASHMIRI FOLK MUSIC IN PRESERVING CULTURAL IDENTITY AND FOSTERING SOCIAL COHESION - Najar, Manzoor (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kashmiri folk music, with its rich tapestry of melodic traditions and lyrical storytelling, plays a pivotal role in preserving the cultural heritage and identity of the Kashmir Valley. This research article explores the historical evolution, distinctive features, and socio-cultural significance of Kashmiri folk music. By examining traditional instruments, musical genres, and the narratives encapsulated in folk songs, the study underscores how this musical heritage reflects the region's diverse cultural influences and historical experiences. The research delves into the role of folk music in community gatherings, religious ceremonies, and seasonal festivals, highlighting its function in fostering social cohesion and communal harmony. Through qualitative analysis the article sheds light on the transmission of musical knowledge across generations and the adaptive strategies employed to sustain these traditions in the face of modern challenges. Furthermore, the study addresses the impact of political unrest and socio-economic changes on the folk music landscape, considering how musicians and communities navigate these dynamics to maintain their musical practices. The research concludes by advocating for the preservation and promotion of Kashmiri folk music as an integral part of the region's intangible cultural heritage, emphasizing the need for collaborative efforts between local communities, cultural organizations, and policymakers.